Arkipäivän kokemuksia köyhyydestä -kirjoituskilpailu 2006 - Mikkonen, Juha; Mikkonen, Juha; Isola, Anna-Maria; Larivaara, Meri; Tiede, taide ja köyhä kansa ry; Isola, Anna-Maria; Larivaara, Meri; Tiede, taide ja köyhä kansa [Association for Science, Art and the Poor]; Finnish Social Science Data Archive (Aineistot, jotka eivät kuulu sarjaan)
The data contain over 800 writings on the conditions and experiences of poverty in Finland. They were written for a writing competition organised specially by the original researchers to collect individual experiences of people affected by poverty. The writings were in different forms, mostly autobiographical narratives but there was some fiction and poetry as well. Voluntary sample. The main theme in the narratives was coping with daily life with little money. For instance, how to manage to pay the rent and the bills and still have enough money for food. Some narratives covered poverty in the author's childhood. Many texts criticised the Finnish welfare system. The dataset is only available in Finnish.
Keywords: debts; everyday life; living conditions; poor persons; poverty; social disadvantage; social security; unemployment; Social sciences; Social welfare policy; Equality, inequality and social exclusion